Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which values of [tex]\(x\)[/tex] satisfy the equation [tex]\(4x^2 + 4x + 1 = 9\)[/tex], we will substitute each given value into the equation and check whether the left-hand side equals 9.
Let's check each option one by one:
Option A: [tex]\(x = \sqrt{10} + \frac{1}{2}\)[/tex]
1. Substitute [tex]\(x = \sqrt{10} + \frac{1}{2}\)[/tex] into the equation:
[tex]\[ 4\left(\sqrt{10} + \frac{1}{2}\right)^2 + 4\left(\sqrt{10} + \frac{1}{2}\right) + 1 \][/tex]
2. Calculate [tex]\(4\left(\sqrt{10} + \frac{1}{2}\right)^2\)[/tex]:
[tex]\[ 4\left(10 + \sqrt{10} + \frac{1}{4}\right) = 4\left(10.25 + \sqrt{10}\right) \approx 40.25 + 4\sqrt{10} \][/tex]
3. Calculate [tex]\(4\left(\sqrt{10} + \frac{1}{2}\right)\)[/tex]:
[tex]\[ 4\sqrt{10} + 2 \][/tex]
4. Combine these:
[tex]\[ 40.25 + 4\sqrt{10} + 4\sqrt{10} + 2 + 1 = 43.25 + 8\sqrt{10} \neq 9 \][/tex]
Thus, Option A does not satisfy the equation.
Option B: [tex]\(x = -2\)[/tex]
1. Substitute [tex]\(x = -2\)[/tex] into the equation:
[tex]\[ 4(-2)^2 + 4(-2) + 1 \][/tex]
2. Calculate [tex]\(4(-2)^2\)[/tex]:
[tex]\[ 4 \cdot 4 = 16 \][/tex]
3. Calculate [tex]\(4(-2)\)[/tex]:
[tex]\[ -8 \][/tex]
4. Combine these:
[tex]\[ 16 - 8 + 1 = 9 \][/tex]
Thus, Option B satisfies the equation.
Option C: [tex]\(x = \frac{\sqrt{2}}{2}\)[/tex]
1. Substitute [tex]\(x = \frac{\sqrt{2}}{2}\)[/tex] into the equation:
[tex]\[ 4\left(\frac{\sqrt{2}}{2}\right)^2 + 4\left(\frac{\sqrt{2}}{2}\right) + 1 \][/tex]
2. Calculate [tex]\(4\left(\frac{\sqrt{2}}{2}\right)^2\)[/tex]:
[tex]\[ 4 \cdot \frac{2}{4} = 2 \][/tex]
3. Calculate [tex]\(4\left(\frac{\sqrt{2}}{2}\right)\)[/tex]:
[tex]\[ 2\sqrt{2} \][/tex]
4. Combine these:
[tex]\[ 2 + 2\sqrt{2} + 1 \neq 9 \][/tex]
Thus, Option C does not satisfy the equation.
Option D: [tex]\(x = -\sqrt{10} + \frac{1}{2}\)[/tex]
1. Substitute [tex]\(x = -\sqrt{10} + \frac{1}{2}\)[/tex] into the equation:
[tex]\[ 4\left(-\sqrt{10} + \frac{1}{2}\right)^2 + 4\left(-\sqrt{10} + \frac{1}{2}\right) + 1 \][/tex]
2. Calculate [tex]\(4\left(-\sqrt{10} + \frac{1}{2}\right)^2\)[/tex]:
[tex]\[ 4\left(10 - \sqrt{10} + \frac{1}{4}\right) = 4\left(10.25 - \sqrt{10}\right) \approx 40.25 - 4\sqrt{10} \][/tex]
3. Calculate [tex]\(4\left(-\sqrt{10} + \frac{1}{2}\right)\)[/tex]:
[tex]\[ -4\sqrt{10} + 2 \][/tex]
4. Combine these:
[tex]\[ 40.25 - 4\sqrt{10} - 4\sqrt{10} + 2 + 1 = 43.25 - 8\sqrt{10} \neq 9 \][/tex]
Thus, Option D does not satisfy the equation.
Option E: [tex]\(x = 1\)[/tex]
1. Substitute [tex]\(x = 1\)[/tex] into the equation:
[tex]\[ 4(1)^2 + 4(1) + 1 \][/tex]
2. Calculate [tex]\(4(1)^2\)[/tex]:
[tex]\[ 4 \][/tex]
3. Calculate [tex]\(4(1)\)[/tex]:
[tex]\[ 4 \][/tex]
4. Combine these:
[tex]\[ 4 + 4 + 1 = 9 \][/tex]
Thus, Option E satisfies the equation.
Option F: [tex]\(x = \sqrt{2}\)[/tex]
1. Substitute [tex]\(x = \sqrt{2}\)[/tex] into the equation:
[tex]\[ 4(\sqrt{2})^2 + 4(\sqrt{2}) + 1 \][/tex]
2. Calculate [tex]\(4(\sqrt{2})^2\)[/tex]:
[tex]\[ 4 \cdot 2 = 8 \][/tex]
3. Calculate [tex]\(4(\sqrt{2})\)[/tex]:
[tex]\[ 4\sqrt{2} \][/tex]
4. Combine these:
[tex]\[ 8 + 4\sqrt{2} + 1 \neq 9 \][/tex]
Thus, Option F does not satisfy the equation.
### Conclusion
The solutions to the equation [tex]\(4x^2 + 4x + 1 = 9\)[/tex] are:
- [tex]\(x = -2\)[/tex]
- [tex]\(x = 1\)[/tex]
So the correct answers are:
B. [tex]\(x = -2\)[/tex]
E. [tex]\(x = 1\)[/tex]
Let's check each option one by one:
Option A: [tex]\(x = \sqrt{10} + \frac{1}{2}\)[/tex]
1. Substitute [tex]\(x = \sqrt{10} + \frac{1}{2}\)[/tex] into the equation:
[tex]\[ 4\left(\sqrt{10} + \frac{1}{2}\right)^2 + 4\left(\sqrt{10} + \frac{1}{2}\right) + 1 \][/tex]
2. Calculate [tex]\(4\left(\sqrt{10} + \frac{1}{2}\right)^2\)[/tex]:
[tex]\[ 4\left(10 + \sqrt{10} + \frac{1}{4}\right) = 4\left(10.25 + \sqrt{10}\right) \approx 40.25 + 4\sqrt{10} \][/tex]
3. Calculate [tex]\(4\left(\sqrt{10} + \frac{1}{2}\right)\)[/tex]:
[tex]\[ 4\sqrt{10} + 2 \][/tex]
4. Combine these:
[tex]\[ 40.25 + 4\sqrt{10} + 4\sqrt{10} + 2 + 1 = 43.25 + 8\sqrt{10} \neq 9 \][/tex]
Thus, Option A does not satisfy the equation.
Option B: [tex]\(x = -2\)[/tex]
1. Substitute [tex]\(x = -2\)[/tex] into the equation:
[tex]\[ 4(-2)^2 + 4(-2) + 1 \][/tex]
2. Calculate [tex]\(4(-2)^2\)[/tex]:
[tex]\[ 4 \cdot 4 = 16 \][/tex]
3. Calculate [tex]\(4(-2)\)[/tex]:
[tex]\[ -8 \][/tex]
4. Combine these:
[tex]\[ 16 - 8 + 1 = 9 \][/tex]
Thus, Option B satisfies the equation.
Option C: [tex]\(x = \frac{\sqrt{2}}{2}\)[/tex]
1. Substitute [tex]\(x = \frac{\sqrt{2}}{2}\)[/tex] into the equation:
[tex]\[ 4\left(\frac{\sqrt{2}}{2}\right)^2 + 4\left(\frac{\sqrt{2}}{2}\right) + 1 \][/tex]
2. Calculate [tex]\(4\left(\frac{\sqrt{2}}{2}\right)^2\)[/tex]:
[tex]\[ 4 \cdot \frac{2}{4} = 2 \][/tex]
3. Calculate [tex]\(4\left(\frac{\sqrt{2}}{2}\right)\)[/tex]:
[tex]\[ 2\sqrt{2} \][/tex]
4. Combine these:
[tex]\[ 2 + 2\sqrt{2} + 1 \neq 9 \][/tex]
Thus, Option C does not satisfy the equation.
Option D: [tex]\(x = -\sqrt{10} + \frac{1}{2}\)[/tex]
1. Substitute [tex]\(x = -\sqrt{10} + \frac{1}{2}\)[/tex] into the equation:
[tex]\[ 4\left(-\sqrt{10} + \frac{1}{2}\right)^2 + 4\left(-\sqrt{10} + \frac{1}{2}\right) + 1 \][/tex]
2. Calculate [tex]\(4\left(-\sqrt{10} + \frac{1}{2}\right)^2\)[/tex]:
[tex]\[ 4\left(10 - \sqrt{10} + \frac{1}{4}\right) = 4\left(10.25 - \sqrt{10}\right) \approx 40.25 - 4\sqrt{10} \][/tex]
3. Calculate [tex]\(4\left(-\sqrt{10} + \frac{1}{2}\right)\)[/tex]:
[tex]\[ -4\sqrt{10} + 2 \][/tex]
4. Combine these:
[tex]\[ 40.25 - 4\sqrt{10} - 4\sqrt{10} + 2 + 1 = 43.25 - 8\sqrt{10} \neq 9 \][/tex]
Thus, Option D does not satisfy the equation.
Option E: [tex]\(x = 1\)[/tex]
1. Substitute [tex]\(x = 1\)[/tex] into the equation:
[tex]\[ 4(1)^2 + 4(1) + 1 \][/tex]
2. Calculate [tex]\(4(1)^2\)[/tex]:
[tex]\[ 4 \][/tex]
3. Calculate [tex]\(4(1)\)[/tex]:
[tex]\[ 4 \][/tex]
4. Combine these:
[tex]\[ 4 + 4 + 1 = 9 \][/tex]
Thus, Option E satisfies the equation.
Option F: [tex]\(x = \sqrt{2}\)[/tex]
1. Substitute [tex]\(x = \sqrt{2}\)[/tex] into the equation:
[tex]\[ 4(\sqrt{2})^2 + 4(\sqrt{2}) + 1 \][/tex]
2. Calculate [tex]\(4(\sqrt{2})^2\)[/tex]:
[tex]\[ 4 \cdot 2 = 8 \][/tex]
3. Calculate [tex]\(4(\sqrt{2})\)[/tex]:
[tex]\[ 4\sqrt{2} \][/tex]
4. Combine these:
[tex]\[ 8 + 4\sqrt{2} + 1 \neq 9 \][/tex]
Thus, Option F does not satisfy the equation.
### Conclusion
The solutions to the equation [tex]\(4x^2 + 4x + 1 = 9\)[/tex] are:
- [tex]\(x = -2\)[/tex]
- [tex]\(x = 1\)[/tex]
So the correct answers are:
B. [tex]\(x = -2\)[/tex]
E. [tex]\(x = 1\)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.